Political Identity Over Personal Impact: Early U.S. Reactions to the COVID-19 Pandemic - Collins, Robert N.; Mandel, David R.; Schywiola, Sarah S. (Frontiers in Psychology, 2021)
Research suggests political identity has strong influence over individuals’ attitudes and beliefs, which in turn can affect their behavior. Likewise, firsthand experience with an issue can also affect attitudes and beliefs. A large (N = 6,383) survey (Pew Research and Ipsos W64) of Americans was analyzed to investigate the effects of both political identity and personal impact on individuals’ reactions to the COVID-19 pandemic. Results show that political identity (i.e., Democrat or Republican) and personal impact (i.e., whether they suffered job or income loss) influenced American public’s attitudes about and response to COVID-19. Consistent with prior research, political identity exerted a strong influence on self-reports of emotional distress, threat perception, discomfort with exposure, support for restrictions, and perception of under/overreaction by individuals and institutions. The between Democrats and Republican responses were consistent with their normative value differences and with the contemporary partisan messaging. Personal impact exerted a comparatively weaker influence on reported emotional distress and threat perception. Both factors had a weak influence on appraisal of individual and government responses. The dominating influence of political identity carried over into the bivariate relations among these self-reported attitudes and responses. In particular, the appraisal of government response divided along party lines, tied to opposing views of whether there has been over- or under-reaction to the pandemic. The dominance of political identity has important implications for crisis management and reflects the influence of normative value differences between the parties, partisan messaging on the pandemic, and polarization in American politics.